Robert Trueman’s Defence of Higher-Order Logic - Tkaczyk, Marcin (Logic and Logical Philosophy, 2023)
The paper contains a review and a discussion of Robert Trueman’s book Properties and Propositions: The Metaphysics of Higher-Order Logic, Cambridge University Press, 2021, pp. xii + 227. ISBN 978-1-108-81410-2. The discussion is focused on the consistency of Truema’s language-based ontology and on its value in defending higher-order logic.